Maternal Cardiac Disease and Perinatal Outcomes in a Single Tertiary Care Center - Ezveci, Huriye; Doğru, Şükran; Akkuş, Fatih; Metin, Ülfet Sena; Gezginc, Kazim (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Objective This study aims to compare the perinatal outcomes of pregnant women with heart disease and a healthy pregnant control group, as well as the maternal and newborn outcomes of pregnant women with congenital heart disease and acquired heart disease.Material method Pregnant women with heart disease and healthy control pregnant women were included in this retrospective study. Sociodemographic data of all patients included in the study were obtained from electronic records. Perinatal outcomes of all patients were compared.Results A total of 258 pregnant women were included in the study. While 129 pregnant women were diagnosed with heart disease, 129 patients were low-risk pregnant women. Preeclampsia (p=0.004) and cesarean section (p=0.01) rates were higher in pregnant women with heart disease compared to healthy pregnant women. Compared with healthy pregnant women, pregnant women with heart disease had a lower birth weight (p=0.003), a higher fetal growth restriction (FGR) rate (p=0.036), lower birth percentiles (p=0.002), a lower 5-minute APGAR (p=0.0001), a higher neonatal intensive care unit (NICU) admission rate (p=0.001), and a longer NICU stay rate (p=0.001). The mean gestational age at birth of pregnant women with congenital heart disease was higher than that of those with acquired heart disease (p=0.017).Conclusion It was observed that all maternal heart diseases were associated with adverse perinatal outcomes compared to healthy pregnant women. In this series, perinatal adverse outcomes of pregnant women with congenital and acquired heart disease did not differ. Keywords: acquired heart disease, congenital heart disease, pregnancy
Keywords: acquired heart disease; congenital heart disease; pregnancy